A naturalistic epistemology selected papers - Kornblith, Hilary (Oxford Univ. Press, 2014)
This volume draws together influential work by Hilary Kornblith on naturalistic epistemology. The naturalistic approach sees epistemology not as a matter of analysis of concepts, but as an explanatory project constrained and informed by work in the cognitive sciences. These essays expound and defend Kornblith's distinctive view of how we come to have knowledge of the world. He offers critical discussion of alternative approaches, such as foundationalism, the coherence theory of justification, internalism, and externalism; and he discusses social epistemology, the role of intuitions in philosophical theorizing, epistemic normativity, and the ways in which philosophical theories may be informed by empirical considerations. Kornblith aims to show how an epistemology which is based in the sciences of cognition may provide the understanding and intellectual illumination which has always been the goal of philosophical theorizing